Comparing Legal Approaches: Mental Disorders as Grounds for Excluding Criminal Responsibility - Stuckenberg, Carl-Friedrich (Bergen Journal of Criminal Law & Criminal Justice, 2016)
The effect of mental disorders on criminal responsibility seems to be more or less the same in all jurisdictions. However, upon a closer look, the details of the regulatory schemes and the practical effects vary considerably and this discord has increased even more in the past 30 years. This article undertakes a brief comparative survey with a focus on substantive criminal law in order to sketch a normative matrix which shows that there are three basic approaches to deal with mental disorders as grounds for excluding criminal responsibility. While psychiatry has made considerable progress over the past 150 years, in providing more humane treatment to mentally ill persons, it is a disturbing observation that the criminal law appears to be significantly less tolerant towards mentally disturbed offenders in modern times than during the previous two millennia.